2007
DOI: 10.1088/0957-0233/18/7/014
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric spectroscopy of watermelons for quality sensing

Abstract: Dielectric properties of four small-sized watermelon cultivars, grown and harvested to provide a range of maturities, were measured with an open-ended coaxial-line probe and an impedance analyser over the frequency range from 10 MHz to 1.8 GHz. Probe measurements were made on the external surface of the melons and also on tissue samples from the edible internal tissue. Moisture content and soluble solids content (SSC) were measured for internal tissue samples, and SSC (sweetness) was used as the quality factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 9 publications
6
54
0
2
Order By: Relevance
“…Radio frequency energy penetrates deeper in mangoes compared to microwaves and, thus, is more suited for potential postharvest disinfestation treatment of this fruit (Sosa-Moralesa et al 2009). Measured dielectric properties and sweetness of freshly harvested melons by soluble solids content with an open ended coaxial-line probe and an impedance analyser over the frequency range from 10 MHz to 1.8 GHz at 25°C and reported that correlations were low for both the dielectric constant and the loss factor at most frequencies (Nelson et al , 2007. A new electrical method is proposed for density sorting of spherical fruits, which measures the volume by electric capacity and mass by electronic balance.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Radio frequency energy penetrates deeper in mangoes compared to microwaves and, thus, is more suited for potential postharvest disinfestation treatment of this fruit (Sosa-Moralesa et al 2009). Measured dielectric properties and sweetness of freshly harvested melons by soluble solids content with an open ended coaxial-line probe and an impedance analyser over the frequency range from 10 MHz to 1.8 GHz at 25°C and reported that correlations were low for both the dielectric constant and the loss factor at most frequencies (Nelson et al , 2007. A new electrical method is proposed for density sorting of spherical fruits, which measures the volume by electric capacity and mass by electronic balance.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Another Brix sensing technique by measuring electric properties of watermelon are correlated with soluble solid content (Nelson et al, 2007). But these modern technologies are more expensive to be use at small scale cultivations.…”
Section: Introductionmentioning
confidence: 99%
“…Presowing treatment of soybean seeds with a pulsed electric field was winter wheat [4], carried out [5][6], onion seeds [7][8], beans and corn [9][10], cotton seeds [11] and etc. In laboratory and field experiments an increase in seed germination to 12 % was obtained; productivity up to 15 % [12; 13].…”
Section: Introductionmentioning
confidence: 99%